Straightforward RAFT Procedure for the Synthesis of Heterotelechelic Poly(acrylamide)s. Issue 4 (9th December 2013) - Wallyn, Sofie; Zhang, Zhiyue; Driessen, Frank; Pietrasik, Joanna; De Geest, Bruno G.; Hoogenboom, Richard; Du Prez, Filip E.; Lutz, J.‐F.; Sumerlin, B.; Matyjaszewski, K.
<x xml:space="preserve">Abstract</x> Heterotelechelic, hydrophilic polymers with a primary amine and thiol group at the α– and ω‐chain end, respectively, are synthesized via reversible addition–fragmentation chain transfer (RAFT) polymerization in a straightforward and versatile way and subsequently used for the design of dual‐responsive polymer/gold nanohybrids. Therefore, a phthalimido‐containing chain transfer agent (CTA) is synthesized and used for the polymerization of the hydrophilic monomers N‐isopropylacrylamide (NIPAM) and N, N‐dimethylacrylamide (DMA). After polymerization, the trithiocarbonate functionality at the ω‐chain end, originating from the CTA, is converted into a thiol upon aminolysis. In the next step, the phthalimido α‐chain end is hydrolyzed into a primary amine, resulting in heterotelechelic, hydrophilic polymers. End‐group conversions are monitored by 1H NMR spectroscopy, MALDI‐TOF MS analysis, and UV–Vis spectroscopy, confirming that quantitative modifications are obtained during each stage. The amino groups of these heterotelechelic polymer chains are modified with citraconic anhydride, after which the obtained polymers are grafted with the thiol group onto citrate‐stabilized gold nanoparticles resulting in the creation of dual‐temperature‐ and pH‐responsive gold particles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>